Growth, instability and sources of output growth of ginger in Karnataka- An analysis: Growth & instability of ginger in Karnataka - Gali, Basavaraj; Reddy, Rakesh (Journal of Spices and Aromatic Crops, 2025)
The present study was undertaken to examine the growth and instability of area, production and productivity of ginger in the state with a special focus on Bidar district of Karnataka. The findings of the study have shown that both growth in area and yield of ginger in Karnataka were positive for study period. However, instability in area, production and productivity was found to be high in period II compared to period I. For overall period, the instability was categorized as high for area, production and yield of ginger in Karnataka. Further, analysis indicates that area is the contributing factor for output growth rather that yield and interaction effect. For several decades, about 70-80 per cent the area under ginger cultivation in the state is dominated by varieties Rio- de – janero, Himagiri and Humnabad local. This suggests that there is significant scope for varietal improvement of ginger. Also, anecdotal evidence indicates that there is significant crop loss due to soft rot disease, inadequate management practices, biotic and abiotic factors leading to high instability in production.